Public Awareness on Cancer-Associated Thrombosis among the Greek Population: First Findings from the ROADMAP-CAT Awareness Study - Souliotis, Kyriakos; Golna, Christina; Nikolaidi, Sofia; Dreden, Patrick V.; Vatheia, Georgia; Gerotziafas, Grigoris T. (TH Open, 2022)
Background Cancer-associated thrombosis (CAT) is the second cause of mortality after cancer itself. CAT is underestimated as a health challenge among oncologists, whereas the levels of awareness among patients and the public have not been systematically assessed and followed in the European Union countries.Aim The Prospective Risk Assessment and Management of Patient with CAT (ROADMAP-CAT) Awareness study is an investigator-initiated, descriptive and nonexperimental study with a cross-sectional design and it explores CAT risk awareness among cancer patients and the general public in Greece to provide an impetus for health policy interventions and a benchmark against which impact of any future interventions may be assessed.Methods A total of 1,003 participants aged above 18 years were contacted by phone after random selection from the national telephone catalogue. Participation was voluntary and completely anonymous, and a structured questionnaire was used to elicit responses. Data were analyzed using IBM SPSS version 25.Results Among respondents, almost one-third (32.3%) reported CAT awareness, while only one in five (21.7%) were aware of the signs and symptoms of venous thromboembolism (VTE). Among patients with a personal history of cancer or of VTE, 47 and 58%, respectively, were aware of CAT risk. Of those aware of the association, 35.2% identified their treating physician as the main source of information. The level of awareness did not significantly differ by responders' demographics.Conclusion The ROADMAP-CAT Awareness study revealed very low levels of awareness on CAT and VTE risk both among the general public and cancer patients in Greece. Awareness of the signs and symptoms of VTE was also particularly low. Treating physicians are not actively engaging in educating their patients about CAT. Public awareness of the increased risk of VTE among cancer patients is critical to prevent and diagnose the disease early. It is imperative that a structured campaign supports medical professionals to take the time to increase awareness and educate their patients on this matter if to improve morbidity and mortality of cancer patients.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; cancer; public awareness